Gradient and categorical assimilation of pretonic vowels in Brazilian Portuguese. (11th November 2020) - Madruga, Magnun Rochel; Hamann, Silke; Abaurre, Maria Bernadete Marques
Abstract : This paper addresses the acoustic realisations of the pretonic vowels /e, o/ that have been previously reported to undergo regressive vowel harmony in Brazilian Portuguese. It examines how the height of pretonic /e, o/ is affected by the phonological and phonetic height of the adjacent stressed vowel in three dialects: Northeastern (Bahia), Northern (Amazonas) and Southern (Rio Grande do Sul). A pseudoword reading task was performed with two speakers each of the three different dialects. The findings suggest that there is some kind of low harmony, in that /e, o/ are realized with markedly higher F1 before the stressed low vowels /ɛ, a, ɔ/ than before the stressed non-low vowels /i, e, o, u/. This effect was found for all dialects, but appears to be categorical (and thus phonological) for the Northern and Northeastern speakers, while gradient for the Southern speakers, where it is likely due to phonetic V-to-V coarticulation. More importantly, no effect of height harmony was found in any of the dialects: pretonic /e, o/ were not produced significantly higher before a stressed /i, u/. In addition, Northern and Southern speakers showed V-to-V coarticulation for the non-high pretonic vowels, illustrating with Northern speakers that a categorical harmony process can co-occur together with a gradient vowel assimilation in the same dialect.